Multi-Target Location for Intelligent Reflecting Surface Aided Radar System - Zhao, Yangying; Chen, Peng; Cao, Zhenxin (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2023)
The target location can be realized based on the estimated directions of arrival (DOAs) when using multiple arrays. However, this leads to the increase of radar system cost. Meanwhile, the location precision depends on the high accuracy of DOA estimations, which are usually with high computational complexity. In this paper, the problem of low-cost system and low-complexity DOA estimation method are addressed. First, a low-cost intelligent reflecting surfaces (IRSs) aided radar location system is developed, where only one fully functional receiving channel is adopted. Then, a novel nonconvex-based atomic norm minimization (NC-ANM) problem is formulated by exploiting the targets' sparsity in the spatial domain to estimate the DOA more efficiently. After getting the DOA estimations, a multi-target location method is proposed. Simulation results show that the proposed NC-ANM method outperforms the compared methods in the DOA estimation with lower computational complexity and achieves accurate location in the IRSs aided system.